Detection of Immunoglobulin G and M Antibodies to Helicobacter Pylori in Serum by an Enzyme Immunoassay Method - Pakshan Hassan (مجلة التربية والعلم, 1999)
ABSTRACT The aim of this study was to detect Helicobacter pylori infection using an enzyme-linked immunosorbent assay (ELISA) to determine whether serological tests can be used for diagnosis. Serum samples were collected from 88 patients (ages ranges between 20 to 75 years) attending for gastrointestinal endoscopy in Erbil hospitals for detection of anti-Helicobacter pylori specific IgG and IgM antibodies in these specimens. IgG and IgM were positive in 44(50%) and 74 (84.09%), respectively. Biopsy specimens were collected from 40 (45.45%) of these 88 patients. The presence or absence of current H. pylori infection was determined by culture, urease and gram stain, that were positive in 37.5%, 82.5% and 20%, respectively which compared with their IgG(85%) and IgM(95%) respectively. The sensitivity, specificity and accuracy of the assay for serum IgG to H. pylori were 94%, 70% and 90% respectively.